La nueva escuela rural unidocente - Mirta Díaz-Forbice (Revista Electrónica Educare)
This research has been developed in coordination with SIMED, a project for improving the quality of education, and the National Office for the Support of multi-grade classrooms. The main objective was to identify the lever of achievement reached in the development of the thirteen strategies forming part of the model at the leading school in a sample of thirty schools chosen from the eighty-six participating in the project. The most important conclusions of this study include the educators´ high degree of identification with their work, the interest that they have in further training, and the support ha the project received from both parents and children. With reference to the development of strategies, the most successful are the drafting of annual plans, lesson planning and institutional management. The least developed include the educational project in institutions, flexible evaluation and promotion, and the work carried out with parents.